استخدام الأشغال الفنية التشكيلية لتنمية بعض المهارات الحركية الدقيقة لطفل الروضة - عبدالحليم، ماجدة هاشم بخيت; درويش، محمد عبدالباسط محمد; محمود، هنية محمود علي Ali, Haniah Mahmoud; أبو زيد، أسماء محمود محمد Abu Zaid, Asma Mahmoud Mohammed (جامعة أسيوط - كلية التربية للطفولة المبكرة, 2022)
هدف البحث: التعرف على فاعلية الأشغال الفنية التشكيلية لتنمية بعض المهارات الحركية الدقيقة لطفل الروضة. عينة البحث: اقتصرت مجموعة البحث الحالية على مجموعة مكونة من عينة (30) طفل وطفلة من أطفال المستوى الثاني (KG 2) بإحدى الروضات التابعة لمديرية التربية والتعليم بروضة مدرسة الراشدة الابتدائية بالداخلة بمحافظة الوادي الجديد في الفصل الدراسي الثاني من العام الدراسي 2020/ 2021 م. منهج البحث: تم استخدام المنهج شبه التجريبي: ذو التصميم الواحد، وذلك عند إجراء تجربة البحث وتطبيق أدواته؛ لبيان استخدام برنامج الأشغال الفنية التشكيلية (كمتغير مستقل) في تنمية بعض المهارات الحركية الدقيقة لطفل الروضة (كمتغير تابع). ١-الدقيقة لطفل الروضة (كمتغير تابع). أدوات البحث ومواده: قامت الباحثة بإعداد الأدوات والمواد التالية: - استطلاع رأي للمعلمات ولأولياء الأمور لتحديد مدى وعيهم ومعرفتهم بالمهارات الحركية الدقيقة لطفل الروضة. - قائمة ببعض المهارات الحركية الدقيقة اللازم تنميتها لطفل الروضة. - مقياس مصور ملون للمهارات الحركية الدقيقة لطفل الروضة. - بطاقة ملاحظة أداء المهارات الحركية الدقيقة المناسبة لطفل الروضة. - كراسة أنشطة المعلمات لتنمية المهارات الحركية الدقيقة لطفل الروضة. - إعداد برنامج الأشغال الفنية التشكيلية لتنمية المهارات الحركية الدقيقة لطفل الروضة. نتائج البحث: توصلت نتائج البحث الحالي إلى وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي درجات التطبيقين القبلي والبعدي لمقياس المهارات الحركية الدقيقة لطفل الروضة على المجموعة التجريبية لصالح التطبيق البعدي، وأيضا وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي درجات التطبيقين القبلي والبعدي لبطاقة ملاحظة المهارات الحركية الدقيقة لطفل الروضة على المجموعة التجريبية لصالح التطبيق البعدي، وكذلك وجود علاقة ارتباطية موجبة قوية دالة إحصائيا عند مستوى دلالة (0.01) بين المقياس وبطاقة الملاحظة. Objectives of research: To determine the impact and effectiveness of the figurative artwork program in order to develop specific motor skills of kindergarten children. Research sample: The current research group was limited to a group of 30 children and 2 kg 2 children in one of the kindergartens of the Directorate of Education in the kindergarten of al-Rashida Elementary School inside the New Valley governorate in the second semester of the 2020/2021 academic year. Research Approaches: 1- quasi-experimental approach: Single design, when conducting research experiment and applying its tools; To illustrate the use of the plastic artwork program (as an independent variable) in developing some of kindergarten children's fine motor skills (as a dependent variable). Research tools and materials: 1. An opinion survey of teachers and parents to determine their awareness and knowledge of the fine motor skills of the kindergarten child. 2. List of some fine motor skills that need to be developed for a kindergarten child. 3. A color photographic scale of the kindergarten child's fine motor skills. 4. A performance note card of fine motor skills appropriate for the kindergarten child. 5. A brochure for teachers’ activities to develop the fine motor skills of the kindergarten child. 6. Preparation of a program of figurative Art Works to develop children's fine motor skills. Kindergarten. Research results: The results of the current research found statistically significant differences at (0.01) between the mean scores of the pre - and post application on the pictured fine motor skills scale to the experimental group for dimensional application, statistically significant differences at (0.01) between the mean scores of the pre - and post application on the Precise Motor Skills to the experimental group for dimensional application, and a statistically significant positive correlation between the Precise Motor Skills and the observation card at (0.01).
Keywords: التعليم الأساسي -- التربية الحركية -- مرحلة رياض الأطفال